Mr. Brown Can Moo! Can You? - Dr Seuss (HarperCollins Children's Books, 2012)
Mr. Brown is an expert at imitating all sorts of noises. There isn't a sound Mr. Brown can't do, from a hippo's gum chewing to a goldfish's kiss. The noisemakers are graphically illustrated and the sound effects are printed in big lettering.
Keywords: Juvenile literature-Fiction